1991
DOI: 10.1111/j.1600-079x.1991.tb00007.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of melatonin on the cell cycle kinetics and “estrogen‐rescue” of MCF‐7 human breast cancer cells in culture

Abstract: Melatonin has been shown to have a direct inhibitory action on the proliferation of estrogen-responsive MCF-7 human breast cancer cells in culture. In the present study, we examined by flow cytometry whether this inhibitory effect might be exerted on the G1 phase of the cell cycle, thus causing a transition delay into the S phase. In order to further verify this hypothesis we tested the ability of estradiol to "rescue" MCF-7 cells from melatonin inhibition, and the potential of this indoleamine to block the ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
88
0
1

Year Published

1997
1997
2009
2009

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 143 publications
(95 citation statements)
references
References 14 publications
6
88
0
1
Order By: Relevance
“…Melatonin, in the presence of normal serum or estradiol, has been shown to retard or block the progression of cells from G0-G1 into S phase; thus, when cells are incubated with 1 nM melatonin, an accumulation of cells in G0-G1 together with a decrease in the population of cells in S phase can be observed (Cos et al 1991, García-Rato et al 1999. Melatonin also increases the length of the MCF-7 cell cycle from 20.36 ± 0.52 to 23.48 ± 0.03 h (Cos et al 1996).…”
Section: Evidence From In Vitro Studies On Human Breast Cancer Cellsmentioning
confidence: 99%
“…Melatonin, in the presence of normal serum or estradiol, has been shown to retard or block the progression of cells from G0-G1 into S phase; thus, when cells are incubated with 1 nM melatonin, an accumulation of cells in G0-G1 together with a decrease in the population of cells in S phase can be observed (Cos et al 1991, García-Rato et al 1999. Melatonin also increases the length of the MCF-7 cell cycle from 20.36 ± 0.52 to 23.48 ± 0.03 h (Cos et al 1996).…”
Section: Evidence From In Vitro Studies On Human Breast Cancer Cellsmentioning
confidence: 99%
“…It has been demonstrated that melatonin counteracts the effects of oestrogens on mammary tumoral cells, thus behaving as a selective oestrogen receptor modulator (SERM). Furthermore, melatonin regulates the expression and activity of the aromatase, the main enzyme responsible for the local synthesis of oestrogens, thus behaving as a selective oestrogen enzyme modulator (SEEM) (Cos et al, 1991(Cos et al, , 2006aMartínez-Campa et al, 2005).…”
mentioning
confidence: 99%
“…3 In vitro, melatonin, at concentrations corresponding to the physiologic levels present in human blood during the night, inhibits proliferation, increases expression of p53 and reduces the invasiveness of the estrogen-responsive MCF-7 human breast cancer cells. [3][4][5][6][7][8][9] Different hypotheses, including the immunomodulatory actions of melatonin, 10 its antioxidative effects 11 or the inhibition of telomerase activity, 12 have been postulated to explain the oncostatic properties of melatonin. However, the effects of melatonin on mammary cancer have been mostly considered as a consequence of its interaction with the estrogen-signaling pathway 13 by 2 different mechanisms: (i) by downregulating gonadal synthesis of steroids and, consequently, decreasing their circulating levels; 2,4 (ii) by interacting with the estrogen receptor, decreasing its expression and inhibiting the binding of the estradiol-estrogen receptor complex to the estrogen-response element on the DNA, thus behaving as a selective estrogen receptor modulator.…”
mentioning
confidence: 99%